2020
DOI: 10.1016/j.watres.2020.115754
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the mechanisms underpinning solids breakthrough in UASB configured anaerobic membrane bioreactors to mitigate fouling

Abstract: In this study, the mechanisms for solids breakthrough in upflow anaerobic sludge blanket (UASB) configured anaerobic membrane bioreactors (AnMBRs) have been described to establish design parameters for limiting membrane fouling. As the sludge blanket develops, two periods can be identified: (i) an initial progressive enhancement in solids separation provided through sludge blanket clarification, via depth filtration, which sustains downstream membrane permeability; and (ii) sludge blanket destabilisation, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Their results indicated that DWW contains an energy generation potential of 7.6 kJ/L (Heidrich et al, 2011). Anaerobic technologies, including the up-flow anaerobic sludge blanket (UASB) and anaerobic MBR (AnMBR) based on the anaerobic digestion (AD) (Smith et al, 2014;Wang et al, 2020), and microbial electrochemical technologies (METs) including microbial fuel cells (MFCs), MECs and microbial recycling cells (MRCs) (Vadillo et al, 2013), are the main advancement in energy production from wastewater.…”
Section: Energy Production From Organicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results indicated that DWW contains an energy generation potential of 7.6 kJ/L (Heidrich et al, 2011). Anaerobic technologies, including the up-flow anaerobic sludge blanket (UASB) and anaerobic MBR (AnMBR) based on the anaerobic digestion (AD) (Smith et al, 2014;Wang et al, 2020), and microbial electrochemical technologies (METs) including microbial fuel cells (MFCs), MECs and microbial recycling cells (MRCs) (Vadillo et al, 2013), are the main advancement in energy production from wastewater.…”
Section: Energy Production From Organicsmentioning
confidence: 99%
“…Among the anaerobic technologies, AnMBR is more efficient than conventional AD systems in biogas production and is currently in potential for practical application (Wang et al, 2020). The combined process of AnMBR and anammox has shown high effectiveness in energy production, where anammox could preserve OC from the denitrification (Dai et al, 2015).…”
Section: Energy Production From Organicsmentioning
confidence: 99%
“…Most common AnMBR-UASB configurations include the membrane module in an external tank [49,98,117,144,145] or at the top of the UASB reactor [77,146,147]. The former is the most reported system.…”
Section: Membrane Coupled At the Top Of The Anmbr-uasbmentioning
confidence: 99%
“…The operational problems reported by operators in regards to typical UASB reactors using granulated sludge became the basis for the search for new technological solutions. The stated shortcomings of UASB systems involve the high cost of obtaining the anaerobic sludge inoculum [34]; the long adaptation period of the microbial biomass [35]; the absolute need to remove fats and suspensions before the wastewater is introduced into the anaerobic chamber [36]; the lack of separation of the phases, requiring different technological conditions for the fermentation process [37]; a sometimes too-small gas exchange surface [38]; the destruction of the granulated sludge and its removal outside the reactor [39]; the clogging of the space between the anaerobic sludge granules [40]; and the inability to effectively remove phosphorus compounds, which are an element limiting the eutrophication of natural water reservoirs [41]. Hybrid reactors can be a competitive and often technologically justified alternative.…”
Section: Introductionmentioning
confidence: 99%